A Clinico-Microscopic Corroboration Of Surgical Repigmentation - A Study Of 30 Cases - Lahiri Koushik; Sengupta Sujit Ranjan (Wolters Kluwer Medknow Publications, 1998)
A total of 30 cases of stable vitiligo with a positive response to punch grafting constituted the sample population. Nineteen of them were female and eleven male, age ranged between 12 and 45 years. Sixteen to twenty weeks after punch grafting, a biopsy each from normal, vitiligenous and surgically repigmented areas, were performed. Sections were studied microscopically using H&E and mason-fontana stains. The microscopic findings demonstrated a district clinico-microscopic corroboration between normal and surgically induced repigmented sites in cases of stable vitiligo.